Nonpharmacological interventions for children with attention deficit hyperactivity disorder in India: A comprehensive and comparative research update - Sujata Satapathy; Vandana Choudhary; Renu Sharma; Rajesh Sagar (Indian Journal of Psychological Medicine, 2016)
The nonpharmacological treatments for children with attention deficit hyperactivity disorder (ADHD) have witnessed a sea change from a rudimentary and haphazard psychosocial to cognitive interventions to social and behavioral skills to body oriented interventions to more sophisticated neurocognitive interventions. As the objective of each treatment varied, the method or procedure of each treatment also differed across studies. Indian research although not very rigorous, did witness changes emphasizing on exploring interventions in reducing symptoms and improving overall behavior. The research literature between 2005 and 2015 was searched using PubMed, Google Scholar, IndMED, MedIND, ResearchGate, and other indexed databases. Results of 110 studies were organized into five broad categories of themes of interventions such as psychosocial, body-focused, cognitive/neuro-cognitive, and cognitive behavioral. Effects of ADHD on cognitive, academic, and behavioral outcomes were also highlighted before the themes of intervention to establish linkage with discussion. However, a limited number (n = 9) of reported Indian studies focusing either on the impact of ADHD on the function of children or on interventions were found, suggesting a huge gap between global and Indian research in the area of children with ADHD. It also highlights the need for development and efficacy testing of indigenous intervention program in different areas of intervention for research and clinical practice.